Prognostic value of heart rate variability in post-infarction patients - Bošković Aneta; Belada Nataša; Knežević Božidarka (Vojnosanitetski Pregled)
Background/Aim. Depressed heart rate variability (HRV) indicating autonomic disequilibrium and propensity to ventricular ectopy can be useful for risk stratification in patients following acute myocardial infarction (AIM). The aim of the study was to assess heart rate variability as a predictor of allcause mortality in post-infarction patients. Methods. We analyzed the 24-hour electrocardiographic (ECG) recordings of 100 patients (80 males) during hospitalization for AIM. The mean age of patients was 56.99 + 11.03 years. Time domain heart rate variability analysis was obtained from 8 to 13 days after index infarction by mean of a 24- hour ECG recording, and the calculated parameters were: standard deviation of all normal to normal RR intervals (SDNN), RRmax-RRmin (difference between the longest RR interval and the shortest RR interval), mean RR interval. We also analyzed ventricular premature complexes from the ECG data. The patients underwent clinical evaluation, laboratory tests and echocardiography. Results. Within a oneyear follow-up period 11 patients experienced death, 10 of them because of cardiac reason and one because of stroke. There were significantly lower values of SDNN (60.55 ± 12.84 ms vs 98.38 ± 28.21 ms), RRmax-RRmin (454.36 ± 111.00 ms vs 600.99 ± 168.72 ms) and mean RR interval (695.82 ± 65.87 ms vs 840.07 ± 93.97 ms) in deceased patients than in the survivors, respectively (p < 0.01). The deceased patients were of higher mean age, with lower left ventricular ejection fraction (0.46 ± 0.05 vs 0.56 ± 0.06 in survivors), and more frequent clinical signs of heart failure and ventricular ectopic activity (> 10VPCs/h; p < 0.01). Multivariate Cox analysis showed that SDNN was a significant, independent predictor of all-cause mortality in postinfarction patients. The other independent predictors were clinical signs of heart failure - Killip class II and III and ventricular ectopic activity. Conclusion. Depressed HRV is an independent predictor of mortality in post-infarction patients and may provide useful additional prognostic information in non-invasive risk stratification of these patients.